Economic Development and Canada’s Gateways: A Tale of Two Regional Development Agencies - Elsibai, Khadeja; Montsion, Jean; De Fuentes, Claudia; Hall, Peter; Brunelle, Dorval (Canadian Journal of Regional Science / Revue canadienne des sciences régionales, 2023)
The Atlantic Canada Opportunities Agency (ACOA) and Western Economic Diversification Canada (WD) are regional development agencies (RDAs) created to forge links between federal economic development priorities and local interests. RDAs in Canada follow a pro-trade agenda in support of local economic growth, but their strategies were adjusted in the 1990s to a new regionalism mindset, which emphasizes decentralized and collaborative leadership. In this article, we examine how both agencies responded, respectively, to the 2007 federal designation of an Atlantic Gateway on the East Coast, and an Asia Pacific Gateway on the West Coast. We combine a content analysis of each RDA’s yearly reports from 2007 to 2020, with a network analysis of their involvement in gateway projects funded by the federal government during this period. The combined analyses show the centrality of ACOA in gateway initiatives in Atlantic Canada, and the peripheral role of WD in Asia Pacific gateway initiatives.